Effects of Hydrogen-Rich Water on Interleukin-1β, Number of Osteoclasts and Osteoblasts in Streptozotocin-induced Diabetic Rats with Orthodontic Tooth Movement - Lina Hadi; Albert Manggading Hutapea; Florenly Florenly (Indonesian Biomedical Journal, 2023)
BACKGROUND: Orthodontic tooth movement (OTM) may increase the risk of treatment-related complications for some diabetes mellitus (DM) patients. Hydrogen-rich water (HRW) has been demonstrated in many studies to reduce oxidative stress and cell damage. This study aimed to examine the levels of interleukin (IL)-1β, blood glucose level, body weight, tooth displacement, and population of osteoclasts and osteoblasts in diabetic rats with OTM.